Study of BOD, COD and TSS Removal in Batik Industry Wastewater using Electrocoagulation Method - Elvinda Bendra Agustina; Abdul Hakim Prima Yuniarto (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2022)
Central Java, especially Pekalongan, is one of the largest batik centres with a high amount of batik waste and has the potential to pollute the environment. Wastewater treatment using the electrocoagulation method as an alternative to environmental pollution prevention in Pekalongan Regency. This study determined the effect of stress and resistance time on decreasing COD, BOD and TSS levels in batik wastewater. The analysis performed on the samples included BOD (Biological Oxygen Demand), COD (Chemical Oxygen Demand), TSS (total suspended solids), and pH. Voltage variations of 12, 24, and 30 volts and holding times of 90, 120, 150, and 180 minutes were applied. A pair of aluminium metals (Al-Al) was used with a thickness of 0.1 cm, an area of 12x14 cm, and a volume of 2500 ml. The results showed that the voltage and contact time decreased the amount of COD, BOD and TSS. In addition, the results showed that the electrocoagulation method at a voltage of 30 volts and a contact time of 180 minutes could reduce COD levels by 75.78%, TSS levels by 93.9%, and BOD levels by 83.75%.